2021
DOI: 10.3390/ijms22042040
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the Auxin Precursor Indole-3-Acetamide Curtails Growth through the Repression of Ribosome-Biogenesis and Development-Related Transcriptional Networks

Abstract: The major auxin, indole-3-acetic acid (IAA), is associated with a plethora of growth and developmental processes including embryo development, expansion growth, cambial activity, and the induction of lateral root growth. Accumulation of the auxin precursor indole-3-acetamide (IAM) induces stress related processes by stimulating abscisic acid (ABA) biosynthesis. How IAM signaling is controlled is, at present, unclear. Here, we characterize the ami1 rooty double mutant, that we initially generated to study the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 110 publications
0
24
0
Order By: Relevance
“…However, despite the severely reduced IAM contents of cyp79b2 cyp79b3 plants [62], both IAOx and AMI1 impaired mutants, exhibited minor IAA altered levels under standard conditions [71]. Herein, excluding the upregulation of YUC8 and ILL5/IAR3, no other significant differentially expressed auxin homeostasis-related genes were identified in ami1-2 [61].…”
Section: Alternative Roads To Iaa Biosynthesismentioning
confidence: 87%
See 4 more Smart Citations
“…However, despite the severely reduced IAM contents of cyp79b2 cyp79b3 plants [62], both IAOx and AMI1 impaired mutants, exhibited minor IAA altered levels under standard conditions [71]. Herein, excluding the upregulation of YUC8 and ILL5/IAR3, no other significant differentially expressed auxin homeostasis-related genes were identified in ami1-2 [61].…”
Section: Alternative Roads To Iaa Biosynthesismentioning
confidence: 87%
“…Strikingly, it was found that, normally germinating homozygous ami1 rty parentals, set a reduced number of siliques producing non-viable seeds. The offspring aborted germination just after radicle extrusion [71]. Consistently, it had to be concluded that impaired nutrient acquisition during seed filling was most probably inherited from heterozygous rty ancestors, thus explaining the parentals sterility.…”
Section: Alternative Roads To Iaa Biosynthesismentioning
confidence: 88%
See 3 more Smart Citations